Evaluasi Program Mahasiswa Wirausaha (PMW) di Universitas Negeri Jakarta - Nuwrile Ard Khiyari; Wahyu Sri Ambar Arum; Siti Zulaikha (Program Studi Manajemen Pendidikan, 2017)
This research aims to give a description and information about EntrepreneurStudent Program (PMW) that has been held at Jakarta State University. This evaluationresearch uses Context, Input, Process and Product (CIPP) model with evaluativeapproach and descriptive method. Data were collected through observations, interviews,questionnaire, documentation study that have been done in Jakarta State University. Theresult of research shows Entrepreneur Student Program has been well done and met theevaluation criteria; 1) evaluation result in program background, goal and need analysishas met the evaluation criteria and shows good in category but legal basis of the programmanagement team should be made, 2) evaluation result in program human resources,objective and infrastructure of program has met the evaluation criteria but clearorganizational structure should be made and human resources who are committed andcompetent in program implementation, 3) evaluation result in program preparation,provision, business run, monitoring and evaluation has met the evaluation criteria but theprogram management team need to monitor the performance of mentor and monitoringand evaluation team so that goal of monitoring and evaluation be achieved with goodimplementation, 4) evaluation result in program result and report has met the evaluationcriteria but concrete efforts should be made to encourage the formation of organizationsthat specifically manages entrepreneurship program.